1999
DOI: 10.1302/0301-620x.81b1.8880
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Hounsfield value for CT-based design of custom femoral stems

Abstract: CT and advanced computer-aided design techniques offer the means for designing customised femoral stems. Our aim was to determine the Hounsfield (HU) value of the bone at the corticocancellous interface, as part of the criteria for the design algorithm. We obtained transverse CT images from eight human cadaver femora. The proximal femoral canal was rasped until contact with dense cortical bone was achieved. The femora were cut into several sections corresponding to the slice positions of the CT images. After o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…A cut-off value of 672 HU was assigned to distinguish cortical (HU4672) from cancellous (HUo672) bone. This value was determined visually by the investigator (KLT) and agrees well with published data (Aamodt et al, 1999). Density was assigned based on HU and was used to calculate elastic modulus using the following equations (Lotz et al, 1990;Snyder and Schneider, 1991;Wirtz et al, 2000):…”
Section: Model Developmentmentioning
confidence: 69%
“…A cut-off value of 672 HU was assigned to distinguish cortical (HU4672) from cancellous (HUo672) bone. This value was determined visually by the investigator (KLT) and agrees well with published data (Aamodt et al, 1999). Density was assigned based on HU and was used to calculate elastic modulus using the following equations (Lotz et al, 1990;Snyder and Schneider, 1991;Wirtz et al, 2000):…”
Section: Model Developmentmentioning
confidence: 69%
“…Although the mean bone density was higher in the maxillary second molar region than in the maxillary first molar region (1,392 Âą522 HU vs. 1,275 Âą 380 HU), the difference was not statistically significant. It has been suggested that bone density values greater than 600 HU indicate dense trabecular bone [1]. The knowledge of the bone density is very important, the positive outcome for osseointegration depending mainly on it.…”
Section: Discussionmentioning
confidence: 99%
“…Kalender [9] states a range of 200 to 250 HU for the lower threshold of bone segmentation. Aamodt et al [10] found a threshold of 600 HU to be suitable for accurate segmentation of femoral cortical bone. Segmentation of temporal bone is described with a lower threshold as low as 150 HU [11] and as high as 3000 HU [12].…”
Section: Segmentationmentioning
confidence: 99%